Ir(triscarbene)-catalyzed sustainable transfer hydrogenation of levulinic acid to γ-valerolactone - Sung, Kihyuk; Lee, Mi hyun; Cheong, Yeon Joo; Jang, Hye Young (Applied Organometallic Chemistry, 2021)
Sustainable iridium-catalyzed transfer hydrogenation using glycerol as the hydride source was employed to convert levulinic acid to γ-valerolactone (GVL) with exceptionally high turnover numbers (TONs) (500,000) and turnover frequencies (TOFs) (170,000 h−1). The highly efficient triscarbene-modified iridium catalysts demonstrated good catalytic activities with low catalyst loadings (0.7 ppm) and good recyclability with an accumulated TON of over two million in the fourth reaction. In addition to glycerol, propylene glycol (PG), ethylene glycol (EG), isopropanol (IPA), and ethanol (EtOH) successfully transferred hydrides to levulinic acid, producing GVL with TONs of 339,000 (PG), 242,000 (EG), 334,000 (IPA), and 208,000 (EtOH), respectively. Deuterium-labeling experiments were conducted to gain insight into the reaction mechanism.
Keywords: Catalyst loadings; Deuterium labeling; Iridium catalyst; Propylene glycols; Reaction mechanism; Transfer hydrogenations; Turnover frequency; Turnover number; iridium complex; sustainable reaction; transfer hydrogenation; triscarbene ligand; γ-valerolactone